Crude Price Changes and Nigeria’s Foreign Reserves, 2008-2023 - LINUS, Justin Ogbonna; LAWAL, Faith Chidinma; Sunday O. Okafor (Archives of Current Research International, 2024)
The study investigated the correlational association between crude price and foreign reserves using the Nigerian economy as the jurisdiction of interest. The study covered the period 2008 to 2023 representing a 25year period. Bivariate pairwise correlational matrix was used to find that a highly significant positive linear association exists between crude price and foreign reserves. Following the findings arising from this study, it is recommended that the country should take advantage of crude price movement in building its foreign reserves given that increase in crude price will likely lead to a rise in revenue from crude sale. A high foreign reserve can act as stabilization fund for exchange rate, debt management and other shocks from international financial flows. Building foreign reserves can be beneficial in managing such exposures to the advantage of the Nigerian economy.